Prevalence of migraine, its effect, and some comorbid psychiatric disorders among female medical students at Al-Azhar University in Cairo - Eman Saif; Reda El-Belbasy; Zeinab El-Sayed Hammour; Mahasen Mohamed (Wolters Kluwer Medknow Publications, 2017)
Background The study on the importance of being mentally, socially, and physically healthy as a medical student is a deficient area in the scientific research in developing countries. Migraine has a negative effect on the general health as well as educational performance. Medical students, especially females, may be at a higher risk to manifest migraine associated with anxiety and/or depression. Aims The aims of this study were to determine the prevalence of migraine headache, to investigate its effect, and to assess some comorbid psychiatric disorders (anxiety and depression) among female medical students at Al-Azhar University in Cairo. Participants and methods A cross-sectional study was carried out on 599 female medical students from grade 1 to grade 6 at Faculty of Medicine for Girls, Al-Azhar University, Cairo, over a period of 1 month during the academic year 2014-2015. The studied female medical students were 18-26 years old. Through a self-administrated questionnaire, sociodemographic data were reported. In students without migraine with aura symptoms, the effects of migraine on daily activities, sleeping pattern, seeking of medical care, educational attendance, and influence on career decision were investigated. For each student, the reported migraine neurological symptoms were verified through meeting the International Headache Society (IHS) criteria for diagnosis, whereas comorbid psychiatric evaluation was assessed through the valid and reliable version of Neuropsychiatric Assessment by Hospital Anxiety and Depression Scale. Results The reported migraine prevalence among the studied female medical students was 35.8%. The mean age of students having migraine was significantly higher than those without migraine (21.09±1.98 vs. 20.61±1.91 years) (P<0.05). Among the students having migraine, 70.2% reported reducing their usual daily activities during migraine episode, 53.5% reported poor sleeping pattern, and 58.6% were found to be felt obliged to attend educational activities despite their migraine symptoms. Seeking medical care was reported by only 20.0% of migraine students. The reported mean episodes of migraine per month was 5.11±4.47. Stress, noise, and menses were the most common triggers of migraine, as recorded by 83.7%. The prevalence of anxiety, depression, and mixed psychiatric disorders among students with migraine was found to be 23.3, 7.4, and 15.4%, respectively, as compared with 20.3, 4.4, and 7%, respectively, among nonmigraine group, without statistically significant differences between them (P>0.05). Conclusion and future vision The prevalence of migraine is considered high among the studied female medical students. It is found to be an important health problem because of its negative effect on diminishing students' performance, disrupting their sleep, and implied stress. Anxiety and/or depression among medicals students with migraine as well as those without are urgent burdens that should be investigated more and targeted by health care providers. Curriculum should include stress-coping tools, counseling, and psychosocial support to reduce distress and severe effect of migraine on students' well-being.